Synthesis and Evaluation of Neoglycoconjugates Based on Adamantyl Scaffolds. Issue 8 (3rd February 2015) - Fleck, Carsten; Memmel, Elisabeth; Fölsing, Moritz; Poll, Bernhard; Hackl, Thomas; Seibel, Jürgen; Maison, Wolfgang
Abstract: Lectin–carbohydrate interactions are important for many biological processes of high pharmaceutical interest. Multivalent carbohydrate conjugates (glycoclusters) have been frequently used to study and manipulate these interactions. In this report, we present the synthesis of trimeric glucose and mannose conjugates that have been assembled with an AB3 scaffold based on adamantane. Several neoglycoconjugates bearing three carbohydrates have been synthesized with different ethylene glycol spacers between the sugar moieties and the adamantyl core. An additional orthogonal functionality at the remaining adamantane bridgehead position allows the conjugation of these trimeric cluster glycosides to other functional molecules such as fluorescent dyes or a solid support for the construction of glycoarrays. We have evaluated the binding properties of trivalent carbohydrate derivatives to ConA as a model lectin in solution by STD‐NMR and on a lectin array by using fluorescent glycoconjugates. Abstract : Neoglycoconjugates based on an adamantyl scaffold have been synthesized. Their binding properties to the plant lectin ConA have been analyzed by STD‐NMR and with a fluorescence‐based binding assay on glass chips. The proposed binding mode is supported by docking calculations.